2010
DOI: 10.1051/0004-6361/201015036
|View full text |Cite
|
Sign up to set email alerts
|

3D MHD simulations of magnetic field evolution and radio polarization of barred galaxies

Abstract: Aims. We study numerically the large-scale gas and magnetic field evolution of barred galaxies in the gravitational potential of a disk, bulge, halo, and bar. We solve non-linear MHD equations including the back-reaction of the magnetic field to the gas. We do not take into account any dynamo process. Methods. We apply the numerical MHD code to calculate the model of the galaxy in three dimensions. We construct realistic maps of high-frequency (Faraday rotation free) polarized radio emission on the basis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
(48 reference statements)
1
9
0
Order By: Relevance
“…For instance, at t = 2.0 Gyr the magnetic spiral is well defined in the interam region, while at t = 5.5 Gyr it is less visible because it connects with magnetic structures apparent in the bar region. The drift of magnetic arms into the interarm area was described in a number of papers e.g., (Kulesza-Żydzik et al 2009(Kulesza-Żydzik et al , 2010, where the authors concluded that this behavior is caused by difference in the angular velocity of magnetic arms and the gaseous spirals. Namely, the magnetic arms do not corotate with gaseous spiral structure, but they follow the general gas motion in the disk, which has a slightly lower angular velocity.…”
Section: Magnetic Field Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, at t = 2.0 Gyr the magnetic spiral is well defined in the interam region, while at t = 5.5 Gyr it is less visible because it connects with magnetic structures apparent in the bar region. The drift of magnetic arms into the interarm area was described in a number of papers e.g., (Kulesza-Żydzik et al 2009(Kulesza-Żydzik et al , 2010, where the authors concluded that this behavior is caused by difference in the angular velocity of magnetic arms and the gaseous spirals. Namely, the magnetic arms do not corotate with gaseous spiral structure, but they follow the general gas motion in the disk, which has a slightly lower angular velocity.…”
Section: Magnetic Field Evolutionmentioning
confidence: 99%
“…Namely, the magnetic arms do not corotate with gaseous spiral structure, but they follow the general gas motion in the disk, which has a slightly lower angular velocity. However, in Kulesza-Żydzik et al (2009Kulesza-Żydzik et al ( , 2010 no dynamo action was included and the drift of magnetic arms into the interam region is not observed during the whole simulation time but only in the short period of calculation.…”
Section: Magnetic Field Evolutionmentioning
confidence: 99%
“…On the theoretical side, the formation and evolution of bar substructure has been extensively studied using numerical simulations on hydrodynamical models (e.g. Sanders & Huntley 1976;Roberts et al 1979;van Albada & Roberts 1981;Athanassoula 1992b;Piner et al 1995;Englmaier & Gerhard 1997;Patsis & Athanassoula 2000;Maciejewski et al 2002;Maciejewski 2004a,b;Regan & Teuben 2003Ann & Thakur 2005;Lin et al 2008;Thakur et al 2009) and magnetized models (e.g., Kulesza-Żydzik et al 2009Kulesza-Żydzik et al , 2010Kulpa-Dybe let al 2011;. In particular, Athanassoula (1992b) confirmed the early notion of Prendergast (1962) that dust lanes are shocks in the gas flows.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of numerical studies on magnetic field distributions in barred galaxies. Depending on how magnetic fields are treated, they can be categorized into two groups: (1) those based on mean-field dynamo theories (e.g., Otmianowska-Mazur et al 1997Moss et al 1998Moss et al , 1999Moss et al , 2001Moss et al , 2007 and (2) those using full magnetohydrodynamic (MHD) simulations (Kulesza-Żydzik et al 2009(Kulesza-Żydzik et al , 2010Kulpa-Dybe l et al 2011). Although numerical models from the first group are successful in obtaining synthetic polarization maps and overall field morphologies comparable to observations, they rely on parameterized turbulent terms in the induction equation that are uncertain.…”
Section: Introductionmentioning
confidence: 99%